The nature of attachment between step-parents and adolescent step-children in the Western Cape: A step-parent's perspective - Mngcangceni, Asisipho (The IIE, 2020)
This study explored the nature of attachment between step-parents and adolescent step-children. This research was based on information gathered from the stepparent's perspective. Interpretivism paradigm and exploratory design were implemented. Participants were recruited in the Western Cape through convenience sampling. Semi-structured interviews were conducted with 10 participants; audio recording and notes were taken. This data was analysed using thematic analysis and the information was organised into themes and patterns. The findings of this study indicate the following: developing relationships with step-children, lack of appreciation, challenging role concerning how to take care of step-children, stepchild's gender and parenting style influenced the interaction between step-parents and adolescent step-children. Future research on the attachments between stepparents and adolescent step-children is required.
Keywords: Familial attachment; Step-parents; Step-children; Adolescents; Perspectives